Bilingualism, cognition, and aging. Issue 1 (27th November 2014) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
<x content-type="archive" xml:space="preserve">Abstract</x> Topics in psycholinguistics and the neurocognition of language rarely attract the attention of journalists or the general public. One topic that has done so, however, is the potential benefits of bilingualism for general cognitive functioning and development, and as a precaution against cognitive decline in old age. Sensational claims have been made in the public domain, mostly by journalists and politicians. Recently (September 4, 2014) The Guardian reported that "learning a foreign language can increase the size of your brain", and Michael Gove, the UK's previous Education Secretary, noted in an interview with The Guardian (September 30, 2011) that "learning languages makes you smarter". The present issue of BLC addresses these topics by providing a state-of-the-art overview of theoretical and experimental research on the role of bilingualism for cognition in children and adults.